Model of Factors that Determine the Perception of the Situation - Savchenko, O. V. (Psychological Prospects Journal, 2011)
The article presents the main provisions of the situational approach to analyzing the behavior of the subject. The author proposed a model of the factors that influence the perception of the situation.